3D spacers enhance flow kinetics in resin transfer molding with woven fabrics. (April 2019) - Salvatori, Damiano; Caglar, Baris; Michaud, Véronique
Abstract: Impregnation time in Resin Transfer Molding (RTM) is directly proportional to resin viscosity and inversely proportional to fabric permeability, limiting the use of high-viscosity resins with conventional reinforcements. In this study, we show how to reduce the impregnation time in RTM by introducing a second solid phase (spacer) in the core of a fabric stack, fabricated by 3D-printing of a polymer phase, which can remain intact or collapse after resin impregnation. An increase of almost two orders of magnitude of the in-plane flow kinetics was obtained, with, however, exacerbated dual-scale flow behavior. The spacers were most effective when an alternative two-step impregnation strategy was adopted, allowing 75% reduction of impregnation time. As proof of concept, two composite plates with spacers made of either poly(lactic acid) (PLA) or polycaprolactone (PCL) were produced via RTM with epoxy resin to demonstrate respectively a stiffening (+20% bending modulus) or collapse of the spacer through melting of the PCL during epoxy cure.